CRITICAL AND INTERSECTIONAL GANG STUDIES - Ortiz, Jennifer M. ([S.l.] : ROUTLEDGE, 2023)
This book offers a critical and empirical examination of gang life, using an intersectional framework considering race, class, gender, and other characteristics. The book reexamines mainstream definitions of gangs, identifies myths and misconceptions, and presents the complex subcultural or countercultural realities of gang members and their associates. Special attention is given to the importance of structural violence experienced by gang members and their communities. This book also interrogates how mainstream gang research is complicit in the oppression of marginalized individuals who join gangs. Assembling contributions from leading experts involved in gang research and the investigation of street gang culture, this book provides a perspective often missing in the conversation around gangs. Direct input from current and former gang members provides a window into the lived experiences of gang life--a picture more accurate and useful than that afforded by the privileged lens often used in gang research. Reliance on an intersectional approach fosters a non-pathological and critical look at gangs and their members. Critical and Intersectional Gang Studies is intended for students and scholars involved in the study of gangs, delinquency, and subcultural theory and will serve as a reference for researchers who wish to utilize a progressive, critical, and intersectional approach to study the impacts of gangs.
OCLC-licensed vendor bibliographic record.
Keywords: Gangs; Gang members; SOCIAL SCIENCE / Criminology